Value Chain of Potato Commodity (Solanum tuberosum) Upland Farmers in Modoinding District, South Minahasa Regency - Caroline B.D. Pakasi; Geraldine C.D. Podung; Mukhlis Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
The research problem is commodity prices, especially at harvest time. The Upland project aims to increase potato production and quality as well as improve access to markets and better selling prices.  This study aims to identify the value chain and its stakeholders, create a graphic design of the value chain in the form of potato marketing channels and analyze the margins in each marketing channel. The research was conducted in Modoinding District, South Minahasa Regency. Sampling using snow ball sampling method, data collection using interview, observation and documentation methods. The results showed that there are 3 levels of marketing channels, including: (1) marketing channel level 0 (farmers - consumers); (2). marketing channel level 2 (farmers - village intermediary traders - inter-island traders - consumers; and there are also farmers - village intermediary traders - large retailers in Modoinding - consumers); and (3) marketing channel level 3 (farmers - village intermediary traders - large traders - inter-island traders - consumers).  The results of the margin analysis showed that the farmer's acceptance value was 100% and the value at the consumer level increased due to the difference in margins with df stakeholders in the marketing channel. The value chain of potato commodities in the South Minahasa Upland Project has the highest margins when farmers sell directly to consumers, and in channels where there is a role of inter-island traders, the highest margin value compared to village intermediaries and large traders.